Evaluasi Sistem Informasi Skripsi dan Tugas Akhir STMIK Primakara (PRISKA) Menggunakan Metode Usability Testing - Ni Luh Dithiana Gitajayanti; I Putu Satwika; A.A. Istri Ita Paramitha (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2021)
Sistem Informasi Primakara Skripsi dan Tugas Akhir (PRISKA) is an information system that created to manage the final project of students in STMIK Primakara. Within the information system, students can manage the process of final project from the beginning until the end. This research is conduct to evaluate PRISKA as information system from the user experience perspectives. To evaluate the information system, researcher will use Retrospective Think Aloud (RTA) and User Experience Questionnaire (UEQ) as the usability testing methods.This research respondent are consist of third year students in STMIK Primakara. The results of this research shows PRISKA that used by students need to be upgraded and develop because student doesn’t give good impressions regarding to the user interface and the user experience